HOSPITAL LAW IN INDONESIA: OPERATIONAL REGULATIONS, MANAGEMENT, AND LEGAL OBLIGATIONS OF HOSPITALS IN ENSURING LEGAL CERTAINTY AND PATIENT PROTECTION BASED ON LAW NUMBER 44 OF 2009 - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2025)
This study analyses the operational arrangements, management, and legal obligations of hospitals in Indonesia based on Law No. 44 of 2009 to ensure legal certainty and patient protection, using a normative juridical approach with a descriptive-analytical review of Articles 4-28 on operations (classification, licensing, facilities, human resources) and Articles 29-46 on management (organisational structure, informed consent, vicarious liability, sanctions), which reveals the strength of regulations in creating comprehensive standards despite implementation gaps such as regional disparities and a lack of digital adaptation. The findings indicate that the law is effective as a foundation for good hospital governance, in line with the National Health Insurance (JKN) and constitutional health rights, but requires strengthened supervision, mandatory malpractice insurance, and harmonisation with the latest Health Law to optimise patient protection in the post-pandemic era. Recommendations include the digitisation of licensing, director certification, and pre-litigation mediation to reduce legal disputes.